Effect of patient education intervention on medication adherence and blood pressure of hypertensive Filipino patients systematic review and meta-analysis - Gutierrez, Margarita M.; Sakulbumrungsil, Rungpetch C. (2021)
"Control of blood pressure because of poor adherence is a problem in the Philippines despite the implementation of medicine access programs. Patient education is utilized to address this problem; however, there is no published literature to evaluate this using a pooled data analysis. The objective of the study is to examine the effect of educational interventions on adherence and blood pressure. Eight databases were used to search for articles published from 2000-2020"-title page.
Includes bibliographical references.
Keywords: Health education -- Philippines; Hypertension -- Philippines; Patient compliance -- Philippines